Role of OSCAR Signaling in Osteoclastogenesis and Bone Disease - Nedeva, Iva R.; Vitale, Mattia; Elson, Ari; Hoyland, Judith A.; Bella, Jordi (Frontiers in Cell and Developmental Biology, 2021)
Formation of mature bone-resorbing cells through osteoclastogenesis is required for the continuous remodelling and repair of bone tissue. In aging and disease this process may become aberrant, resulting in excessive bone degradation and fragility fractures. Interaction of receptor-activator of nuclear factor-κB (RANK) with its ligand RANKL activates the main signalling pathway for osteoclastogenesis. However, compelling evidence indicates that this pathway may not be sufficient for the production of mature osteoclast cells and that co-stimulatory signals may be required for both the expression of osteoclast-specific genes and the activation of osteoclasts. Osteoclast-associated receptor (OSCAR), a regulator of osteoclast differentiation, provides one such co-stimulatory pathway. This review summarises our present knowledge of osteoclastogenesis signalling and the role of OSCAR in the normal production of bone-resorbing cells and in bone disease. Understanding the signalling mechanism through this receptor and how it contributes to the production of mature osteoclasts may offer a more specific and targeted approach for pharmacological intervention against pathological bone resorption.